EXISTENTIAL PHILOSOPHY: PERCEPTION OF HUMAN REALIA AND VALUES - Скальська, Д. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article reveals that art has always been an ideal for existential studies during the analysis of almost all spheres of human life. Overall anthropological history, human realia and values have been perceived through it owing to irrational intuition.